2021
DOI: 10.1071/ah21160
|View full text |Cite
|
Sign up to set email alerts
|

Considering the new minimum staffing standards for Australian residential aged care

Abstract: Objective To compare the historical staffing patterns and organisational characteristics of Australian residential aged care facilities (RACFs) against the new minimum staffing standards recommended by the Royal Commission into Aged Care Quality and Safety (RCACQS). Method Retrospective data analysis was used to compare the staffing levels and characteristics of 1705 RACFs (for 4 years, 2016–19) with the three new mandatory staffing requirements. De-identified datasets were provided by the RCACQS, obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Workforce shortages – a key driver of agency staffing – are already a perennial challenge within the sector and are expected to continue in the next decade 4,26 . In the near term, staffing shortages are likely to be exacerbated as providers attempt to increase staffing levels to meet the incoming mandatory minimum standards, 27 while managing the workforce demands and disruptions from the COVID‐19 pandemic 28 . Another reform that may alter providers' workforce models is the windup of the Aged Care Approval Round programme (‘bed licenses’) in 2024 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Workforce shortages – a key driver of agency staffing – are already a perennial challenge within the sector and are expected to continue in the next decade 4,26 . In the near term, staffing shortages are likely to be exacerbated as providers attempt to increase staffing levels to meet the incoming mandatory minimum standards, 27 while managing the workforce demands and disruptions from the COVID‐19 pandemic 28 . Another reform that may alter providers' workforce models is the windup of the Aged Care Approval Round programme (‘bed licenses’) in 2024 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The participants of this study emphasized the observed benefits of of care to residents living with dementia and end-of-life care needs, suggesting regular staffing patterns were integral to achieving this. However, difficulty with staff retention, as echoed in the findings from our study, remains an enduring problem for the aged care sector (24). The international health services community ought to prioritize research that will assist in building a sustainable aged care workforce capable of withstanding the pressures of an aging population, recognizing and responding to the increasing prevalence of dementia among the cohort, and delivering high-quality palliative and end-of-life care to these people.…”
Section: Discussionmentioning
confidence: 85%
“…As a result of the Royal Commission into Aged Care Quality and Safety, the Australian government has put in place several of its key recommendations. Nearly two-thirds of residential aged care providers are operating at a deficit [ 34 ], and this is partly attributed to a low level of occupancy. Residential aged care providers outside metropolitan areas are heavily affected by increased regulatory compliance, a workforce shortage, and wage pressure and may move away from the provision of residential care, which will further exacerbate the undersupply of this form of care.…”
Section: Discussionmentioning
confidence: 99%